Implementasi Syariat Islam Terhadap Etnis Tionghoa di Aceh (Studi Kasus : Gampong Peunayong, Kecamatan Kuta Alam, Banda Aceh) - Yuni Saputri; Fahrizal; Muhammad Zaini (Journal of Mandalika Literature, 2024)
Aceh is known as the only region in Indonesia that applies IslamicSharia in a strict manner in everyday life. The people of Aceh are indeed veryfamiliar with Islamic Sharia. Because Islamic Sharia has been implementedsince the time of the Islamic kingdom in Aceh. Islamic Sharia is the law thatregulates all aspects of social life. Such as education, economy, social society,culture, lifestyle, food, and household. Islamic Sharia only applies to allMuslims living in Aceh. However, as a sovereign region, Aceh is not onlyinhabited by Muslims or Acehnese people. Several ethnic groups also enliventhe diversity of Acehnese society, one of which is the Chinese ethnic group.Islamic Sharia also regulates non-Muslim people living in Muslim areas. InIslam, this group is called zimmi infidels. So, how do ethnic Chinese live theirreligious life under the umbrella of Islamic Sharia? In this article, the authorwants to explain more deeply the implementation of Islamic Sharia towardsethnic Chinese.